A revision of the Malagasy endemic genus Adetomyrma (Hymenoptera: Formicidae: Amblyoponinae) - Yoshimura, Masashi; Fisher, Brian L. (Zootaxa, 2012)
The species-rank taxonomy of the genus Adetomyrma Ward, 1994 is revised. Nine species are distinguished with eightdescribed as new: A. aureocuprea sp. nov., A. bressleri sp. nov., A. caputleae sp. nov., A. cassis sp. nov., A. caudapinniger sp.nov., A. cilium sp. nov., A. clarivida sp. nov., A. goblin sp. nov. Worker-male associations are identified for all worker-basedspecies: A. bressleri, A. caputleae, A. goblin along with A. venatrix Ward, 1994 from which the male is described for the firsttime. Five new species are described only from males. An ergatoid queen of Adetomyrma is described for the first time. Keys to species for workers and males are given.